1987
DOI: 10.3109/07420528709083530
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Once-Daily Evening Versus Morning Sustained-Release Theophylline Dosing For Nocturnal Asthma

Abstract: Eight diurnally active (approximately 0730-1100 hr) adults (41-61 yr) suffering from nocturnal asthma volunteered for a double-blind, cross-over randomized study of a once-daily dosing (600-900 mg/24 hr) of Armophylline (Rorer s.a., France), a sustained-release theophylline given either at 0800 hr or 2000 hr for 8-day durations. Study variables monitored daily were: (a) self-measured peak expiratory flow (PEF), heart rate, oral temperature and self-rated fatigue checked every 2 hr during the waking span as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…In the past, sleep logs and VAS have been useful successfully to quantify subjective variables in adults such as fatigue, attention, and drowsiness, for example, in field studies of shift workers (11,12) and patients with nocturnal asthma (13). These methods also have been successfully applied in studies of children as young as 7 years of age to investigate circadian changes in subjective variables (14)(15)(16)(17)(18).…”
Section: Methodsmentioning
confidence: 98%
“…In the past, sleep logs and VAS have been useful successfully to quantify subjective variables in adults such as fatigue, attention, and drowsiness, for example, in field studies of shift workers (11,12) and patients with nocturnal asthma (13). These methods also have been successfully applied in studies of children as young as 7 years of age to investigate circadian changes in subjective variables (14)(15)(16)(17)(18).…”
Section: Methodsmentioning
confidence: 98%
“…Although medication has been recommended after breakfast, the validity of this has not been proved. Knowledge of the circadian rhythms in symptom intensity of chronic disease, along with the chronopharmacology of medications, has been used to optimize conventional once-a-day H2-receptor antagonists for peptic ulcer disease [10], theophylline for nocturnal asthma [11], cholesterol-lowering agents [12], and even cancer medications to lessen their toxicity and enhance therapeutic outcome [13]. However, many doctors and patients are unaware that the effects of certain antihypertensive drugs differ significantly according to the time of day they are ingested.…”
Section: Introductionmentioning
confidence: 99%
“…The recommended daily pattern of dosing is either a single evening dose, or one-third of the daily dose in the morning and two-thirds in the evening. Several studies have shown that the bioavailability of Theophylline is greater if administered in the evening than in the morning, and that such chronotherapy is more effective in preventing the nighttime dip in FEV1 than the conventional Theophylline administration (equally divided daily dose between morning and evening administration)99-101, although this effect may be concentration dependent102. Kraft et al have also shown that administration of Theophylline to subjects with asthma in the evening improved the inflammatory profile of the distal airways, and this was correlated with improved nocturnal FEV1103.…”
Section: Asthmamentioning
confidence: 99%